Fungi associated with two species of Oxalis - Fatema, Yasmin; Shamsi, Shamim (Bangladesh Journal of Scientific Research, 2012)
No abstract available DOI: http://dx.doi.org/10.3329/bjsr.v25i1.13050 Bangladesh J. Sci. Res. 25(1): 53-60, 2012